Evaluasi Kebijakan Disiplin Pegawai Negeri Sipil Dalam Meningkatkan Efektivitas Penyelenggaraan Pemerintahan Di Kota Ternate - Sadik, Mira; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Research in the area of Secretariat and staffing agency areas of ternate city in the framework of the preparation of Thesis in proposing to meet one of the conditions to get a college degree holdersThe discipline policy of civil servants in government agencies at both the environment as well as the area has long been applied through the implementation of the Government Regulation number 53 in 2010 about disciplinary rules, civil servants, but so far it still found the behavior of CIVIL SERVANTS who Deviate even happening abusive authority thus implies a decrease in the performance of CIVIL SERVANTS so affected on the low effectiveness of government organizations themselvesThis research aims to: know the impact of policy discipline of civil servants against effectiveness of running government in the city of ternate . The results of this study are expected to provide benefits, either theoretically or practically, theoretical research results is expected to enrich the development of social science, particularly the study of public administration. in practical research results is also expected to contribute to the thinking of policy makers, in particular for the Government of the city of ternate and other related parties to solve practical problems in particular problems related , either directly or indirectly with the construction of the civil servants in order to increase Work discipline expected positive impact for increasing the effectiveness of the Organization of the Government Fore, ternate city. The conclusion of the Organization of the Government, particularly in the area of Secretariat and staffing agency Area ternate city has done enough effectiveness although not optimal, the results of the analysis of the data showed that between the discipline of employees working with the effectiveness of the Government on Secretariat staffing agencies of regional and city areas of ternate relationship connectedness and influence its nature kontributif as well as the very real or significantAdvice is necessary to provide some suggestion that the first to raise awareness of discipline , then required increase supervision , good functional monitoring to surveillance and , both in government can increase the effectiveness of the optimization work discipline employees other than through , the government also need to activate the city of ternate functional training to improve the quality of human resources employees Keywords: civil servants disciplinary policy & effectiveness of the Organization of the Government